Study of the Use of Local Plants as Food for the Tidung Tribe of Sepala Dalung Village and Its Application in Biology Learning - Ibitanija, Via; Fatmawati, Fatmawati; Sam, Nur Fitriana (Biopedagogia, 2024)
Indonesia, known for its rich diversity of plants, has regions with distinctive food plants. The use of local plants as food remains prevalent among the Tidung people in Sepala Dalung Village, Tana Tidung Regency, North Kalimantan. This study aimed to explore the utilization of local plants as food by the Tidung people in Sepala Dalung Village. The research was descriptive with a qualitative approach, employing interviews, observations, and documentation for data collection. The results revealed that the Tidung Tribe utilized plants from two habitats: 10 plant types from hygrophytic habitats and 3 plant types from hydrophytic habitats. The commonly used plant parts included roots, leaf stems, and fruits. Plant processing was categorized into two types: those that could be consumed directly and those requiring prior processing. The findings highlighted the potential of diversifying local plants as alternative food sources, providing new knowledge for the community in Sepala Dalung Village, which could be incorporated into biology education to enhance learning.